Conceptualization of head-heart-hands model for developing an effective 21st century teacher - Islam, Md. Aminul; Haji Mat Said, Seriaznita Binti; Umarlebbe, Jameela Hanoon; Sobhani, Farid Ahammad; Afrin, Sadia (Frontiers in Psychology, 2022)
Celebrities, athletes and even politicians are frequently identified as role models for most impressionable students. But the reality is, outside of their own home, one of the greatest role models in a student’s life is standing in front of the classroom. Teachers are people to look up to and emulate. This paper attempts to discover some of the essential qualities and skills that would help teachers and the students they teach achieve their full potentials, and also some key characteristics that contribute to teachers and instruction effectiveness. This paper also attempts to highlight the features of 3H (Head, Heart and Hands) model in effective instructional approach and theorises that the 3H attributes in combination with Bloom’s Taxonomy will produce effective 21st century teachers. Hence, this article endeavors to create awareness and contribute to the transformation of teachers towards reflective and visionary; confident and competent teachers. After all, effective teachers will inspire their talented students to live up to their full potentials. Effective 21st century teachers are in the best position to shape and equip students with the desired 21st century skills.